Affinity-based SDS PAGE identification of phosphorylated Arabidopsis MAPKs and substrates by acrylamide pendant Phos-Tag™ - Komis, George; Takáč, Tomáš; Bekešová, Slávka; Vadovič, Pavol; Samaj, Jozef (Methods in molecular biology (Clifton, N.J.), 2014)
Protein phosphorylation is the most abundant and best studied protein posttranslational modification, dedicated to the regulation of protein function and subcellular localization as well as to protein-protein interactions. Identification and quantitation of the dynamic, conditional protein phosphorylation can be achieved by either metabolic labeling of the protein of interest with (32)P-labeled ATP followed by autoradiographic analysis, the use of specific monoclonal or polyclonal antibodies against the phosphorylated protein species and finally by phosphoproteome delineation using mass spectrometry.Hereby we present a fourth alternative which relies on the enforced-affinity-based-electrophoretic separation of phosphorylated from non-phosphorylated protein species by standard SDS-PAGE systems co-polymerized with Phos-Tag™ and Mn(2+) or Zn(2+) cations. Phosphate groups of phosphorylated Ser, Thr, and Tyr residues form complexes with Mn(2+) and Zn(2+) cations with polyacrylamide immobilized Phos-Tag™. Following appropriate treatment of the gels, separated proteins can be quantitatively transferred to PVDF or nitrocellulose membranes and probed with common-not phosphorylation state specific-antibodies and delineate the occurrence of a certain phosphoprotein species against its non-phosphorylated counterpart.
Keywords: Electrophoresis, Polyacrylamide Gel; fosfoproteiny; Mitogen-Activated Protein Kinases; fenol; fosfatasy; Phosphoproteins; polyvinyly; membrány umělé; Polyvinyls; Bacteriophage lambda; Acrylamide; bakteriofág lambda; akrylamid; Membranes, Artificial; Phenol; Culture Techniques; fosforylace; mitogenem aktivované proteinkinasy; kultivační techniky; Arabidopsis; Phosphoric Monoester Hydrolases; elektroforéza v polyakrylamidovém gelu; Phosphorylation